The development of children's literature in the Philippines with an annotated bibliography of children's literature, 1901-1975 - Serina, Loreto M.; Vallejo, Rosa M.; Alabado, Ceres S. C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1976)
This investigation on the growth and development of children's literature in the Philippines is divided into two parts that include a historical development of children's literature in the Philippines from the earliest period to 1975; the biographical sketches of some well-known authors and illustrators of children's books and their views on the status of writing and illustrating children's books; children's books publishing and background information on some active publishing companies; an analysis of the problems and setbacks faced by the publishers of children's books; books on children's literature used by the different schools in the Philippines; and conclusions and recommendations of the study; and an annotated bibliography of children's literature consisting of 428 entries.
The normative-survey method together with personal interviews, survey through questionnaires and researches on written literary materials are used to determine the nature and enormity of the problems and setbacks that affect the development of children's literature in the Philippines.
The most significant aspects of the study are the examination of the results that made possible the analysis of the problems which led to the formulation of concrete solutions and recommendations and the presentation of a comprehensive annotated bibliography of children's books for the Filipinos. The classified bibliography consists of four hundred twenty eight (428) book titles on children's literature published from 1900 up to 1975. The entries under each subject are arranged by authors in alphabetical order, with complete bibliographic information and brief descriptive annotations. After each annotation, the grade level of the book is indicated, whether elementary or secondary. The literary works written in Pilipino and in English are listed separately. The works are divided into four general categories: prose, poetry, anthologies and textbooks or readers, and translations and/or adaptations.
The problems of writing, illustrating and publishing children's books are summarized in the last chapter. Recommendations by authors, illustrators and publishers on how to increase production of children's books are likewise noted. The writer's recommendations on the role of teachers, librarians, parents, government agencies and civic organizations in encouraging the production of more books for Filipino children and the proper utilization of them follow those of the authors, illustrators and publishers interviewed.
Mimeographed.
Vita.
Special Problem (Master of Library Science)
Keywords: Children's literature, Philippine -- Bibliography; Children's literature, Philippine -- History and criticism